Vortex-induced vibration of a 5:1 rectangular cylinder: new computational and mathematical modelling approaches - Nguyen, Dinh Tung (2017)
As a the limit-cycle oscillation, vortex-induced vibration (VIV) does not cause catastrophic failure but it can lead to fatigue in long and slender structures and structural elements, especially for long span bridges. Assessing this behaviour during the design stage is therefore very important to ensure the safety and serviceability of a structure. Currently, this task requires very time-consuming wind tunnel or computational simulation since a reliable mathematical model is not available. Moreover, knowledge of the underlying physical mechanism of the VIV and, particularly, of the turbulence-induced effect on the VIV is insufficient. Turbulence is normally considered to produce suppressing effects on the VIV; however, this influence appears to depend on cross sections and a comprehensive explanation is yet to be found. This issue can be resulted from some limitation that most wind tunnel or computational studies have used sectional models. The flow field is therefore dominated by 2D flow features.